Natural Resistance of Human Immunodeficiency Virus Type 1 to the CD4bs Antibody b12 Conferred by a Glycan and an Arginine Residue Close to the CD4 Binding Loop - Dueñas Decamp, María José; Peters, Paul; Burton, Dennis; Clapham, Paul R. (ASM, 2008)
The human monoclonal antibody b12 recognizes a conserved epitope on gp120 that overlaps the CD4 binding site. b12 has neutralizing activity against diverse human immunodeficiency virus type 1 (HIV-1) strains. However, we recently reported that b12 sensitivity of HIV-1 envelopes amplified from patient tissues without culture varied considerably. For two subjects, there was clear modulation of b12 sensitivity, with lymph node-derived envelopes being essentially resistant while those from brain tissue were sensitive. Here, we have mapped envelope determinants of b12 resistance by constructing chimeric envelopes from resistant and sensitive envelopes derived from lymph node and brain tissue, respectively. Residues on the N-terminal flank of the CD4 binding loop conferred partial resistance. However, a potential glycosylation site at residue N386 completely modulated b12 resistance but required the presence of an arginine at residue 373. Moreover, the introduction of R373 into b12-sensitive NL4.3 and AD8 envelopes, which carry N386, also conferred b12 resistance. Molecular modeling suggests that R373 and the glycan at N386 may combine to sterically exclude the benzene ring of b12 W100 from entering a proximal pocket. In summary, we identify residues on either side of the CD4 binding loop that contribute to b12 resistance in immune tissue in vivo. Our data have relevance for the design of vaccines that aim to elicit neutralizing antibodies.